KONSEP PENDIDIKAN MULTIKULTURAL DALAM PEMIKIRAN NURCHOLISH MADJID (CAK NUR) DAN RELEVANSINYA TERHADAP PENGUATAN PENDIDIKAN INKLUSIF - Binti Mar’atus Sholihah; Itsna Rusydiana (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to analyze the concept of multicultural education in the thought of Nurcholish Madjid (Cak Nur) and to examine its relevance to strengthening inclusive education in Indonesia. The multicultural education proposed by Cak Nur is rooted in the principles of tawhid, humanism, and social justice, which reject all forms of discrimination based on ethnicity, religion, race, or social group. This research employs a qualitative approach using a library research method through content analysis of Cak Nur’s works, such as Islam, Modernity, and Indonesian-ness, as well as related literature on inclusive education. The findings indicate that Cak Nur’s thought emphasizes the importance of pluralism, respect for diversity, and the spirit of dialogue as the foundation of multicultural education. These values have strong relevance in reinforcing the paradigm of inclusive education that positions every learner as an individual with unique potential, free from discrimination. Therefore, Cak Nur’s ideas can serve as a philosophical and ideological foundation for the development of inclusive education policies and practices in Indonesia.